A multistream heat exchanger model with enthalpy feasibility. (12th July 2018) - Tak, Kyungjae; Kwon, Hweeung; Park, Jaedeuk; Cho, Jae Hyun; Moon, Il
Highlights: A multistream heat exchanger model with enthalpy feasibility is proposed. A temperature feasibility constraint is converted into enthalpy feasibility. A physical property package is employed for accurate enthalpy calculations. The developed model exploits monotonically increasing feature of T–H curves. An NG liquefaction process is optimized using the developed model. Abstract: A temperature feasibility constraint is an important part of multistream heat exchanger (MSHE) modeling. However, temperature feasibility of an MSHE model makes a numerical issue when a physical property package is used to obtain highly accurate temperature-enthalpy relationships in equation-oriented modeling environment. To resolve the issue, this study proposes a new MSHE model with enthalpy feasibility using the fact that enthalpy is a monotonically increasing function of temperature. A natural gas liquefaction process, called a single mixed refrigeration process, is optimized using the proposed MSHE model under an equation-oriented modeling environment with a physical property package as a case study.